2003
DOI: 10.1021/ef020151i
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Some Metal Oxides Supported on Alumina with Alternating Methane and OxygenApplication for Chemical-Looping Combustion

Abstract: Chemical-looping combustion (CLC) is a combustion technology with inherent separation of the greenhouse gas CO2. The technique involves the use of a metal oxide as an oxygen carrier, which transfers oxygen from the combustion air to the fuel. Two reactors are used in the process:  (i) a fuel reactor where the metal oxide is reduced by reaction with the fuel, and (ii) an air reactor where the reduced metal oxide from the fuel reactor is oxidized with air. The possibility of using oxides of Cu, Co, Mn, and Ni as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
275
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(277 citation statements)
references
References 7 publications
2
275
0
Order By: Relevance
“…Ni-, Fe-, Cu-, Mn-and Co-based metal oxides are the typical materials to be employed as oxygen carrier for chemical looping process (Mattisson et al, 2003). CaSO 4 was also used for transferring oxygen for methane combustion in fluidized bed reactors (Song et al, 2009 (Adanez et al, 2004).…”
Section: Oxygen Carriers For Chemical Looping Processmentioning
confidence: 99%
“…Ni-, Fe-, Cu-, Mn-and Co-based metal oxides are the typical materials to be employed as oxygen carrier for chemical looping process (Mattisson et al, 2003). CaSO 4 was also used for transferring oxygen for methane combustion in fluidized bed reactors (Song et al, 2009 (Adanez et al, 2004).…”
Section: Oxygen Carriers For Chemical Looping Processmentioning
confidence: 99%
“…In addition, other characteristics such as easy preparation to reduce costs are interesting. Iron, nickel, copper, and manganese have been selected as the most promising active metals to be used in a CLC process [4][5][6]. Also the selection of a suitable support material is very important.…”
Section: Introductionmentioning
confidence: 99%
“…The metal oxides with its reduced metal oxides or metals, which are used as oxygen carriers in the CLC must have sufficient reaction activity in reduction and oxidation and enough strength to limit particle breakage and attrition. A number of metals have been discussed in the literature 21,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] , such as Fe, Ni, Co, Cu, Mn, and Cd, as well as some metal composites. Based on an oxygen transfer capability, energy balance analysis and thermodynamics analysis, copper (Cu) seems to be the better choice as an oxygen carrier for the CLC system of solid fuels.…”
Section: Development Of New Mercurymentioning
confidence: 99%
“…Previous studies indicated that Cu-based oxygen carriers had reactivity of 100 % reduction within minutes at lower temperatures (600-900 o C) [37][38][39][40] in the fixed bed or fluidized bed testing facilities. When copper oxide was doped on substrate, it indicated that most of its oxygen is active for reaction with methane, and the highest efficiency could be achieved with reduction rates up to 100 %/min and oxidation rates up to 25 %/min.…”
Section: Development Of New Mercurymentioning
confidence: 99%